CORPORATE SOCIAL RESPONSIBILITY STRATEGI KOMUNIKASI PERUSAHAAN MIGAS - Mohammad Hidayaturrahman (Jurnal Nomosleca, 2017)
Abstract This research was conducted to find out what kind of communication strategy of oil and gas company in Sumenep, Madura East Java. This research method using single case study with qualitative descriptive approach. This research was conducted by using object observation and interviews to various informants directly related. From the research, it is found that PT Kangean Energi Indonesia (KEI) oil and gas company through single corporate social responsibility (CSR) program model becomes one of effective means of communication. The lack of corporate social responsibility (CSR) single program is not able to cover many problems faced by the community simultaneously, takes a long time to be able to solve other problems. So there needs to be additional funding for the sustainability of the program, and the acceleration of community needs fulfillment. Keywords: CSR, Strategy, and Communication. DOI : https://doi.org/10.26905/nomosleca.v3i2.2036